Allergic contact dermatitis caused by acrylates in nail cosmetic products: Case reports and review of the literatures - Yi-Tsz Lin; Shih-Wei Tsai; Ching-Wen Yang; Yu-Hsian Tseng; Chia-Yu Chu (Wolters Kluwer Medknow Publications, 2018)
Acrylates are esters of acrylic acid, which are potent sensitizers that can cause occupational allergic contact dermatitis (ACD) in dental personnel. More recently, an increasing number of cases of both occupational and non-occupational ACD in beauty industry are observed. Here we present three cases of ACD to acrylate and its derivatives in both nail beauticians and do-it-yourself gel nail users due to exposure to nail cosmetics presenting with chronic hand eczema with severe pulpitis and even nail dystrophy with patch-test-confirmed diagnosis. Chemical analysis of commercial nail cosmetic products has been done in one of the patients and successfully identified 2-hydroxypropyl acrylate as the contact allergen. Keywords: Acrylic acid, Acrylate, Allergic contact dermatitis (ACD), Methacrylate, Nail cosmetic products